Over‐use of thyroid testing in Canadian and UK primary care in frequent attenders: A cross‐sectional study. Issue 6 (28th March 2021) - Crampton, Noah; Kalia, Sumeet; Del Giudice, Maria Elisabeth; Wintemute, Kimberly; Sullivan, Frank; Aliarzadeh, Babak; Meaney, Christopher; Moineddin, Rahim; Singer, Alexander; Hinton, William; Sherlock, Julian; Williams, John; et al.
Abstract: Background: Thyroid‐stimulating hormone (TSH) is a common test used to detect and monitor clinically significant hypo‐ and hyperthyroidism. Population‐based screening of asymptomatic adults for thyroid disorders is not recommended. Objective: The research objectives were to determine patterns of TSH testing in Canadian and English primary care practices, as well as patient and physician practice characteristics associated with testing TSH for primary care patients with no identifiable indication. Methods: In this 2‐year cross‐sectional observational study, Canadian and English electronic medical record databases were used to identify patients and physician practices. Cohorts of patients aged 18 years or older, without identifiable indications for TSH testing, were generated from these databases. Analyses were performed using a random‐effects logistic regression to determine patient and physician practice characteristics associated with increased testing. We determined the proportion of TSH tests performed concurrently with at least one common screening blood test (lipid profile or hemoglobin A1c). Standardised proportions of TSH test per family practice were used to examine the heterogeneity in the populations. Results: At least one TSH test was performed in 35.97% (N = 489 663) of Canadian patients and 29.36% (N = 1 030 489) of English patients. Almost all TSH tests in Canada and England (95.69% and 99.23% respectively) were within the normal range (0.40‐5.00 mU/L). A greater number of patient‐physician encounters was the strongest predictor of TSH testing. It was determined that 51.40% of TSH tests in Canada and 76.55% in England were performed on the same day as at least one other screening blood test. There was no association between the practice size and proportion of asymptomatic patients tested. Conclusions: This comparative binational study found TSH patterns suggestive of over‐testing and potentially thyroid disorder screening in both countries. There may be significant opportunities to improve the appropriateness of TSH ordering in Canada and England and therefore improve the allocation of limited system resources.